From “Female Malady” to an Environmental Condition: Hysteria in the Russian scientific discourse of fin-de-siècle - Sobol, Valeria (Wiener Slawistischer Almanach, 2023)
This article discusses publications on hysteria in the Russian medical andpsychiatric periodicals of the late nineteenth and early twentieth century, focusing onthe demographic characteristics of the hysterical patients (such as gender, ethnicity,class, and race). While the earlier publications frame hysteria decidedly as a “femalemalady,” later a more complex confluence of factors emerges, reflecting the increasingattention to male hysteria in Western neurology and psychiatry and the concomitantstrategies to displace this condition onto ethnic others and protect the healthy nationalbody. Moreover, Russian discourse on hysteria vacillates between the view of thiscondition as a malaise of urban modernity and a sign of backwardness, as manifestedby numerous reports of hysterical “epidemics” among peasants. The gender-informedinterpretation of the disorder persists throughout the period, but it is increasinglyovershadowed by other factors, including racial characteristics and environmentalconditions, as in the case of “Siberian” hysteria. I conclude that, while Russian clinicalwriters actively engaged with the Western discourse on hysteria, their narratives alsochanneled specifically Russian concerns, such as anxiety about Russia’s national body,the empire’s complex encounters with modernity, and its history of political oppression.